Toll-like receptor and C-type lectin receptor agonists attenuate osteogenic differentiation in human dental pulp stem cells - Wajathip Bulanawichit; Chanakarn Sinsareekul; Chatvadee Kornsuthisopon; Ajjima Chansaenroj; Vorapat Trachoo; Nunthawan Nowwarote; Thanaphum Osathanon (BMC, 2024)
Abstract Background This study aimed to investigate the effects of various toll-like receptor (TLR) and C-type lectin receptor (CLR) ligands on osteogenic differentiation in human dental pulp stem cells (hDPSCs). Methods hDPSCs were cultured and treated with various concentrations (0.01, 0.1, 1.0, and 10 µg/mL) of TLR or CLR agonists (PG-LPS, E.coli LPS, poly(I:C), Pam3CSK4, Furfurman, and Zymosan). Cell viability was determined by MTT assay. The effects of TLR and CLR agonists on osteogenic differentiation of hDPSCs were measured by alkaline phosphatase (ALP) activity, Alizarin Red S staining, and Von Kossa staining. In addition, the mRNA expression of osteogenesis-related genes (ALP, COL1A1, RUNX2, OSX, OCN and DMP1) was examined by RT-qPCR. A non-parametric analysis was employed for the statistical analyses. The statistically significant difference was considered when p < 0.05. Results Treatment with TLR and CLR agonists was associated with an increase in hDPSCs' colony-forming unit ability. Compared with the control group, TLR and CLR agonists significantly inhibited the osteogenic differentiation of hDPSCs by decreasing the ALP activity, mineralised nodule formation, and mRNA expression levels of osteogenesis-related genes (ALP, COL1A1, RUNX2, OSX, OCN and DMP1). The inhibition of TRIF but not Akt signalling rescued the effects of TLR and CLR agonist attenuating hDPSCs' mineralisation. Conclusions The activation of TLRs or CLRs exhibited an inhibitory effect on osteogenic differentiation of hDPSCs via the TRIF-dependent signalling pathway.